2020
DOI: 10.1051/radiopro/2020038
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder engagement in the management of indoor radon exposures

Abstract: Radon in buildings poses a significant health risk, being one of the most important causes of lung cancer deaths worldwide. Acknowledging that successful radon risk management requires engagement of stakeholders, this paper investigated prescriptions and practices for stakeholder participation. First, it points out the need to integrate radon risk management in a holistic approach to indoor air pollution, together with urban planning and energy saving policies. It then argues for establishing more systematic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 12 publications
1
8
0
1
Order By: Relevance
“…Some countries/states, for instance, Estonia, only inform people about radon and place the responsibility for behavioral actions on the individual [ 13 ], whereas other countries, for instance, Ireland and Belgium, take the initial steps to include more specific legislation [ 13 , 14 ]. Multiple scholars state that legislation procedures in terms of housing code requirements (comparable to energy efficiency) might increase the uptake for radon testing and mitigating [ 15 , 16 , 17 ], as is the case in certain States in The United States, for instance, Pennsylvania [ 12 ]. On a European level, Austria is considering similar measures [ 13 ].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Some countries/states, for instance, Estonia, only inform people about radon and place the responsibility for behavioral actions on the individual [ 13 ], whereas other countries, for instance, Ireland and Belgium, take the initial steps to include more specific legislation [ 13 , 14 ]. Multiple scholars state that legislation procedures in terms of housing code requirements (comparable to energy efficiency) might increase the uptake for radon testing and mitigating [ 15 , 16 , 17 ], as is the case in certain States in The United States, for instance, Pennsylvania [ 12 ]. On a European level, Austria is considering similar measures [ 13 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other policy measures are mostly concerned with reducing the economic impact of the testing and mitigating procedure—for instance, incentivizing mitigations, offering subventions, or providing free tests [ 15 , 17 ]. A city in Ireland experimented with providing digital radon monitors in the library to facilitate the need for these monitors without the costs of buying them [ 3 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Radon case studies related to communication and stakeholder engagement, presented by Turcanu et al [ 25 ], showed that there are more challenges related to the responsibilities, rules and roles of different actors involved in radon management, which may be barriers for the successful implementation of a radon mitigation strategy. Some of these challenges include the following: the plurality of responsibilities between different authorities; lack of awareness about radon and the associated risks among decision makers and the general public, as well as among key professional stakeholders, such as family doctors, architects, and building professionals; disparities of knowledge, with greater awareness of radon in the highest radon risk areas compared to other areas.…”
Section: Some Gaps In Existing National Radon Control Strategiesmentioning
confidence: 99%
“…Le projet ENGAGE a eu pour objectif d'étudier les modalités d'implication des parties prenantes pour la gouvernance du risque radiologique dans trois situations d'exposition : radon, médical, situations accidentelle et postaccidentelle. Le projet ENGAGE a abouti à la proposition de 14 recommandations dont six sont dédiées à la gestion des situations accidentelle et post-accidentelle (Turcanu et al, 2019). Ces propositions ont été discutées et finalisées à Bratislava lors d'un atelier réunissant plus d'une quarantaine de participants (e.g., partenaires du projet ENGAGE, représentants des plateformes européennes de recherche, de l'AEN-OCDE, de l'AIEA, de l'Organisation mondiale des médecins généralistes, des ONG Greenpeace et SAFECAST ainsi que des parties prenantes françaises).…”
Section: Engage (2017-2019)unclassified